Does the â€œIdaman Jelitaâ€ Character of Universitas Negeri Surabaya Influence Students Economics Literacy? - Rafsanjani, Mohamad Arief; Sholikhah, Ni'matush; Prakoso, Albrian Fiky (Dinamika Pendidikan, 2019)
The purpose of this research is to find out how the influence of students' perceptions about the affirmation of the â€œidaman jelitaâ€ character towards economic literacy, also to exemine the heneral education theory. The population was students majoring in economics education in semester 3, consist of 254 students of 4 study program in the Departement of Economics Education. The sampling technique used was purposive random sampling, with a total of 176. Data analysis techniques using Structural Equation Modeling (SEM). The results of the study are there is a significant and positive effect on the affirmation of the â€œidaman jelitaâ€ character on economic literacy among students of the Department of Economic Education, Faculty of Economics, Universitas Negeri Surabaya. This indicates that the better the affirmation of the â€œidaman jelitaâ€ character, the better the economic literacy of students. Finally we suggests to the next researcher to confirm the results of this study with qualitative methods to dig deeper and detailed information related to the variables studied.